Los medios de comunicación en África: desarrollo de la prensa y prensa del desarrollo - Kabunda, Mbuyi (Revista Española de Desarrollo y Cooperación, 2023)
Media agents, in their classic and nowadays concepts – paper, sound, image, and recent number technology–, are designated to have a fundamental role in economic development and democratic consolidation in Africa, two parallel and connected phenomenon. The following lines intend to analyze such role during the last four decades and try to understand forthcoming perspectives.